2017
DOI: 10.1186/s40562-017-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Ellerman bombs observed with the new vacuum solar telescope and the atmospheric imaging assembly onboard the solar dynamics observatory

Abstract: Ellerman bombs (EBs) are believed to be small-scale reconnection events occurring around the temperature minimum region in the solar atmosphere. They are often identified as significant enhancements in the extended Hα wings without obvious signatures in the Hα core. Here we explore the possibility of using the 1700 Å images taken by the Atmospheric Imaging Assembly (AIA) onboard the Solar Dynamics Observatory (SDO) to study EBs. From the Hα wing images obtained with the New Vacuum Solar Telescope (NVST) on 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In the absence of Hα observations, the 1700 Å continuum can be used as a proxy for EBs (e.g., Vissers et al 2013;Chen et al 2017;Danilovic et al 2017). We searched for EB signatures in AIA 1700 Å using the EBDETECT 3 code (Vissers et al 2019a).…”
Section: Ellerman Bombs As Sub-canopy Eventsmentioning
confidence: 99%
“…In the absence of Hα observations, the 1700 Å continuum can be used as a proxy for EBs (e.g., Vissers et al 2013;Chen et al 2017;Danilovic et al 2017). We searched for EB signatures in AIA 1700 Å using the EBDETECT 3 code (Vissers et al 2019a).…”
Section: Ellerman Bombs As Sub-canopy Eventsmentioning
confidence: 99%
“…The enhancement of the FUV continuum is the most striking feature in our EB simulations. Previous observations confirmed that EBs are visible in the FUV continuum at 1600 Å and 1700 Å (Vissers et al 2013;Rezaei & Beck 2015;Tian et al 2016;Chen et al 2017). And it is very promising to detect EBs from these wavebands (Vissers et al 2019a).…”
Section: The Fuv Continuum Enhancement Of Ebsmentioning
confidence: 68%
“…There have been observations of EBs in 1400 Å, 1600 Å, and 1700 Å images (Vissers et al 2015;Tian et al 2016;Chen et al 2017;Ortiz et al 2020), yet we still expect more to statistically check the visibility in all these three FUV bands, with a particular combination of IRIS and AIA observations. The response of the Hα line in UV bursts (Hansteen et al 2017;Ortiz et al 2020) is also an interesting topic for future observations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chen et al(2017) [85] have carried out a statistical study on the visibility of EBs in the AIA 1700 Å images by using NVST Hα core and off-band images. There are 145 EBs that were identified from Hα wing images, in which 74 EBs (about 51%) can be clearly identified as bright points (BPs) in the AIA 1700 Å images.…”
Section: Ellerman Bombsmentioning
confidence: 99%